Changes of Ammonia, Nitrite and Nitrate at Recirculation System of Red Tilapia (Oreochromis sp.) Rearing - Djokosetiyanto, D.; Sunarma, A.; Widanarni, . (Jurnal Akuakultur Indonesia, 2006)
High rearing density of fish in an intensive culture system require  high amount of feed which may result in the accumulation of organic materials in the water to a higher level. The accumulation of organic materials can  be toxic for fish, generate mineralization of nutrient from organic materials and cause high oxygen expenditure.  Recirculation system is an aquaculture system which aimed to maintain water quality at an appropriate level for fish to survive and grow,   Theammonia concentration in recirculation system with biofilter tended to decrease sharply while there was only a slightly decrease in that without biofilter. Conversion efficacy of ammonia nitrogen (NH3-N)  and nitrite nitrogen (NO2-N) of   biofilter compiled with aeration system was 46.20% and 30.68%, while in an unaerated system was 39.31% and 8.53%, respectively.  The use of aquatic plant was found to be an effective way to reduce nitrate nitrogen (NO3-N).  A higher conversion efficacy of nitrate (50.15%) in the tank containing aquatic plant was observed by using aeration before biofilter. Keywords: ammonia, nitrite, nitrate, recirculation system, red tilapia, Oreochromis sp.   ABSTRAK Padat penebaran tinggi pada sistem budidaya intensif menuntut tingginya jumlah pakan yang diberikan kepada ikan sehingga mengakibatkan penumpukan bahan organik dalam wadah. Akumulasi bahan organik akan menyebabkan terjadinya pembentukan senyawa-senyawa yang beracun bagi ikan, mineralisasi nutrien dari bahan organik dan penyerapan oksigen yang tinggi. Untuk mempertahankan kualitas air sehingga tetap layak bagi ikan, digunakan sistem resirkulasi dalam proses pemeliharaannya. Kecenderungan penurunan konsentrasi ammonia terlihat tajam pada filter biologis pada unit yang menggunakan filter biologis, sedangkan tanpa filter biologis hanya terjadi penurunan konsentrasi ammonia yang kecil sehingga efektifitas pengubahannya menjadi kecil.  Efektivitas pengubahan ammonia (NH3-N) pada filter biologis pada unit tanpa perlakuan aerasi hanya sebesar 39,31% dengan efektivitas pengubahan nitrit (NO2-N) sebesar 8,53%. Sedangkan pada unit yang meggunakan proses aerasi sebelum filter biologis, efektivitas pengubahan ammonia dan nitrit masing-masing mencapai 46,20% dan 30,68%. Penggunaan tanaman akuatik efektif untuk menurunkan konsentrasi nitrat (NO3-N). Efektifitas pengubahan nitrat pada wadah tanaman akuatik tertinggi sebesar 50,15% dicapai oleh unit yang menggunakan sistem aerasi sebelum filter biologis. Kata kunci: ammonia, nitrit, nitrat, resirkulasi, nila merah,  Oreochromis sp.